2019
DOI: 10.1155/2019/8563095
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature on a Boy: Mosaicism with an Isodicentric Y Chromosome

Abstract: Mosaicism brings great variability into the clinical expression of numerical and structural chromosomal abnormalities. The phenotypic variability of 45,X/46,XY mosaicism extends from Turner syndrome to apparently physically normal males. We present a case of a 14-year-old adolescent with short stature and delayed puberty, who was admitted in a Paediatric Endocrinology outpatient clinic. After a careful investigation, he was found to have a 45,X/46,X,idic(Y)(p11.32) mosaicism. This case report emphasizes the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…11 In 45,X/46,XY males, gonadectomy is reserved for patients with sexual ambiguity including cryptorchidism or hypospadias since SRY appears protective against malignancy. 12 Silvestre et al suggested the use of an external masculinization score (EMS) to assess risk of malignancy in 45,X/46,XY patients due to an inverse correlation between higher EMS scores and risk of gonadal malignancy. 12 In males, germ cell tumors are more often associated with intra-abdominal gonads.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 In 45,X/46,XY males, gonadectomy is reserved for patients with sexual ambiguity including cryptorchidism or hypospadias since SRY appears protective against malignancy. 12 Silvestre et al suggested the use of an external masculinization score (EMS) to assess risk of malignancy in 45,X/46,XY patients due to an inverse correlation between higher EMS scores and risk of gonadal malignancy. 12 In males, germ cell tumors are more often associated with intra-abdominal gonads.…”
Section: Discussionmentioning
confidence: 99%
“…12 Silvestre et al suggested the use of an external masculinization score (EMS) to assess risk of malignancy in 45,X/46,XY patients due to an inverse correlation between higher EMS scores and risk of gonadal malignancy. 12 In males, germ cell tumors are more often associated with intra-abdominal gonads. 7 It has been suggested that 45, X/46,XY males with nearly normal external genitalia may be assessed periodically by ultrasound or physical palpation of the gonads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isochromosomes have been reported in prenatal testing and are predominantly observed in advanced maternal age pregnancies [24]. The isodicentric Y chromosome has been associated with variable outcomes for which few reports have found it compatible with a normal male phenotype in absence of other abnormalities [24,25], while other have reported cases with short stature [26] and mixed gonadal dysgenesis [27]. Similarly, isodicentric X chromosome has been reported with a normal female phenotype [28] and refractory anemia in a case of active isodicentric X [29].…”
Section: Isochromosomesmentioning
confidence: 99%